NAFKAH PERSPEKTIF FIQIH DAN UNDANG-UNDANG ; - Sokhi Huda; Ahmad Halimi Masruri (LPPM UNHASY, 2022)
This article is the result of a qualitative field research. This research is a legal sociology research. This article discusses the neglect of livelihoods that occurred in Gedang Hamlet, Tambakrejo Village. Researcher analyzes the research data with fiqh theory and the Undang-undang Perkawinan No.1 1974. The findings of this study are that the neglect of livelihood that occurs in Gedang Hamlet, Tambakrejo Village is included in the category of violation of the income obligation, it can even be included as domestic violence. There are two things to be argued. Ms. LM's husband has not given her a living for 6 months, the second is that Mrs. LM's husband often comes home at night, sometimes even for several days he does not come home. fiqh clearly mentions the categories of earning a living, although with many variations. All fiqh differences of opinion about the limits of living were violated by LM's mother's husband. Law No. 23 of 2004 was also violated in terms of fulfilling the husband's support for his wife. Keyword: living limits, fiqh, the rule of law Daftar Pustaka ————- Al qur’an karim. Departemen Agama, tahun 2015. Al Amin, Habibi.